Period of ‘Iddah Of Woman In Khulu’ Perspective Of Ibn Qayyim Al-Jauziyyah and Ibn Hazm - Nasution, Roihanatunnida; Irwan, Irwan (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
This study discusses the waiting period (‘Iddah) of a woman who initiates divorce through khulu’ according to the perspectives of two prominent scholars, Ibn Qayyim al-jauziyyah and Ibn Hazm. Khulu’ is a form of divorce initiated by the wife with compensation (iwadh) given to the husband. The main issue addressed in this research is the differing opinions between the two scolars regarding the length of the ‘iddah for women who undergo khulu’. Ibn Qayyim asserts that the ‘iddah period is one menstrual cycle, while Ibn Hazm maintains it should be three quru’. This research employs a qualitative method with a library research approach and comparative analysis. The findings indicate that the divergence arises from the difference in their legal reasoning methods: Ibn Qayyim adopts ta’lil (reason-based analogy) and qiyas, while Ibn hazm adheres strictly to the literal meaning of the texts. This study contributes to the understanding of Islamic Legal divercity concerning marital jurisprudence.